Cement-based solid-state electrolyte stack structure power storage method, system, device, and medium
Patent Information
- Application Number
- CN202611074217.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-10-16
AI Technical Summary
但是其在实际使用时,仍旧存在一些缺点,如现有技术在制备电解质层时追求完全水化使得后水化活性被完全消耗,无法在使用过程中进行自我优化或修复;未针对正极侧和负极侧不同的电化学环境和界面应力特征进行差异化设计,导致界面阻抗大、循环过程中易开裂脱粘;未利用外部物理场与电场的协同作用来主动激发水泥材料本身的化学反应能力,离子通道的构建和界面的优化在充电过程中相互脱节,无法形成从材料重构到电荷存储的完整链条
通过非对称温湿度场养护构建梯度水化度的电解质层,使高水化度侧致密稳定、低水化度侧保留大量未水化水泥颗粒,既保证了面向正极侧的结构完整性和抗副反应能力,又为后续负极侧的原位界面融合提供了充足的化学活性位点,解决了现有技术完全水化导致水泥后水化活性被浪费的问题;
Smart Images

Figure CN122931089A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrochemical energy storage technology, and more specifically, to a method, system, device, and medium for energy storage using a cement-based solid electrolyte stacked structure. Background Technology
[0002] Cement-based solid electrolytes are a newly emerging type of energy storage material in recent years. Using silicate cement as a matrix, they utilize the nanopores and layered structures in cement hydration products to achieve ion conduction. Compared with other solid electrolytes, cement-based materials have advantages such as low raw material cost, simple preparation process, non-flammability, and castability, making them particularly suitable for integration with building structures to achieve a fusion of structure and energy storage functions. They show promising application prospects in distributed energy storage and building energy conservation. However, it still has some shortcomings in practical use. For example, the existing technology pursues complete hydration when preparing the electrolyte layer, which completely consumes the post-hydration activity and makes it impossible to self-optimize or repair during use; it does not make differentiated designs for the different electrochemical environments and interfacial stress characteristics of the positive and negative electrode sides, resulting in high interfacial impedance and easy cracking and debonding during cycling; it does not utilize the synergistic effect of external physical fields and electric fields to actively stimulate the chemical reaction ability of the cement material itself, and the construction of ion channels and the optimization of the interface are disconnected during charging, making it impossible to form a complete chain from material reconstruction to charge storage. Summary of the Invention
[0003] In order to overcome the above-mentioned defects of the prior art, the present invention provides a method, system, device and medium for energy storage using a cement-based solid electrolyte stacked structure, and solves the problems mentioned in the background art through the following solutions.
[0004] To achieve the above objectives, the present invention provides the following technical solution: a method for energy storage using a cement-based solid electrolyte multilayer structure, comprising: S1. Silicate cement, alkali metal salt, layered silicate and water are mixed and stirred to obtain a slurry. After being cast into shape, it is cured under asymmetric temperature and humidity field conditions so that the resulting cement-based solid electrolyte layer forms a gradient distribution from high hydration degree to low hydration degree along the thickness direction. S2. The positive electrode, the cement-based solid electrolyte layer, and the negative electrode are stacked in sequence to form a stacked structure. A porous carbon paper layer is provided between the positive electrode and the cement-based solid electrolyte layer as an ion buffer layer. The negative electrode and the cement-based solid electrolyte layer are in direct physical contact. The high hydration degree surface of the cement-based solid electrolyte layer faces the positive electrode and the low hydration degree surface faces the negative electrode. S3. Perform an in-situ electrochemical reconstruction and charging procedure on the stacked structure to obtain the reconstructed stacked structure: S301. The stacked structure is charged with a pulsed current. Through the alternating action of the pulsed electric field, alkali metal ions are driven to migrate directionally along the electric field direction inside the cement-based solid electrolyte layer, thereby constructing a directional ion transport channel in situ. S302. Switch to constant voltage charging mode, apply constant voltage and simultaneously increase ambient humidity to the humidity range that triggers secondary hydration reaction, so that the unhydrated cement particles retained in the cement-based solid electrolyte layer generate a hydration product transition layer in situ at the interface between the low hydration surface and the negative electrode sheet. S303. Maintain constant pressure and reduce ambient humidity to dehydrate and densify the hydration product transition layer, thereby obtaining the reconstructed laminated structure; S4. Perform interface self-healing periodic charge-discharge cycles on the reconstructed stacked structure: After completing N conventional charge-discharge cycles, insert a self-healing cycle. During the self-healing cycle, switch to constant voltage charging mode and simultaneously increase the ambient humidity to the humidity range that triggers the secondary hydration reaction, thereby triggering the supplementary secondary hydration reaction of the unhydrated cement particles to repair the interface microcracks.
[0005] A cement-based solid electrolyte multilayer energy storage system, characterized in that it comprises: The gradient hydration degree electrolyte layer preparation module is used to mix silicate cement, alkali metal salt, layered silicate and water to obtain slurry, and after casting and molding, it is cured under asymmetric temperature and humidity field conditions so that the obtained cement-based solid electrolyte layer forms a gradient distribution from high hydration degree to low hydration degree along the thickness direction. An asymmetric stacked structure assembly module is used to stack a positive electrode, a cement-based solid electrolyte layer, and a negative electrode in sequence to form a stacked structure. A porous carbon paper layer is set between the positive electrode and the cement-based solid electrolyte layer as an ion buffer layer. The negative electrode and the cement-based solid electrolyte layer are in direct physical contact, and the high hydration degree surface of the cement-based solid electrolyte layer faces the positive electrode and the low hydration degree surface faces the negative electrode. An in-situ electrochemical reconstruction charging control module is used to execute an in-situ electrochemical reconstruction charging program on the stacked structure. The in-situ electrochemical reconstruction charging control module is configured to: firstly charge the stacked structure with a pulsed current, and through the alternating action of the pulsed electric field, drive alkali metal ions to migrate directionally along the electric field direction inside the cement-based solid electrolyte layer, and construct directional ion transport channels in situ; then switch to a constant voltage charging mode, apply a constant voltage and simultaneously increase the ambient humidity to the humidity range that triggers the secondary hydration reaction, so that the unhydrated cement particles retained in the cement-based solid electrolyte layer generate a hydration product transition layer in situ at the interface between the low hydration degree surface and the negative electrode sheet; then maintain the constant voltage and reduce the ambient humidity, so that the hydration product transition layer loses water and becomes dense, thus obtaining the reconstructed stacked structure; The self-healing cycle control module is used to perform interface self-healing periodic charge-discharge cycles on the reconstructed stacked structure. The self-healing cycle control module is configured to insert a self-healing cycle after completing N regular charge-discharge cycles. During the self-healing cycle, it switches to constant voltage charging mode and simultaneously increases the ambient humidity to the humidity range that triggers the secondary hydration reaction, thereby triggering the supplementary secondary hydration reaction of the unhydrated cement particles to repair the interface microcracks.
[0006] An electronic device is characterized by comprising: at least one processor, at least one communication bus, a temperature and humidity sensor interface, a voltage and current detection interface, a programmable power drive interface, and a memory; and a computer program stored in the memory and executable on the processor, wherein the computer program, when executed by the processor, implements the cement-based solid electrolyte stacked structure energy storage method.
[0007] A computer-readable storage medium, characterized in that it stores a computer program, which, when executed by a processor, implements the described cement-based solid electrolyte stacked structure energy storage method. The technical effects and advantages of this invention are as follows: By constructing an electrolyte layer with gradient hydration degree through asymmetric temperature and humidity field curing, the high hydration degree side is dense and stable, while the low hydration degree side retains a large number of unhydrated cement particles. This not only ensures the structural integrity and resistance to side reactions facing the positive electrode, but also provides sufficient chemical active sites for the subsequent in-situ interface fusion on the negative electrode side. This solves the problem of the waste of cement hydration activity caused by complete hydration in existing technologies. A porous carbon paper layer is set on the positive electrode side as an ion buffer layer, and direct physical contact is maintained on the negative electrode side to protect the positive electrode side from the ion concentration impact caused by pulse charging. The negative electrode side is reserved for the maximum reaction interface for secondary hydration fusion, which solves the problem that the existing symmetrical interface treatment cannot adapt to the differentiated electrochemical environment of the positive and negative electrodes. The in-situ electrochemical reconstruction charging procedure, which is synergistically regulated by electric field and humidity, simultaneously realizes the directional construction of ion transport channels and the chemical bonding of interfaces during the charging process. This transforms the charging process into a tool for optimizing the microstructure of materials, solving the problem of the disconnect between ion channel construction and interface optimization in existing technologies. By utilizing the unique continuous post-hydration activity of cement materials, self-repair is periodically and actively triggered during charge-discharge cycles, allowing interfacial microcracks to be repeatedly repaired during use. This overcomes the fundamental limitation of other solid electrolyte systems that cannot self-repair, thus extending the cycle life of the device. Attached Figure Description
[0008] Figure 1 This is a schematic diagram of the overall structure of the present invention.
[0009] Figure 2 This is a schematic diagram of the preparation structure of the gradient hydration electrolyte layer of the present invention.
[0010] Figure 3 This is a schematic diagram of the asymmetric stacked assembly structure of the present invention.
[0011] Figure 4 This is a schematic diagram of the in-situ electrochemical reconstruction and self-healing cycle structure of the present invention.
[0012] Figure 5 This is a schematic diagram of the system structure of the present invention.
[0013] Figure 6 This is a schematic diagram of the electronic device structure of the present invention. Detailed Implementation
[0014] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0015] refer to Figures 1-4 The cement-based solid electrolyte stacked structure energy storage method shown includes: S1. Silicate cement, alkali metal salt, layered silicate and water are mixed and stirred to obtain a slurry. After being cast into shape, it is cured under asymmetric temperature and humidity field conditions so that the resulting cement-based solid electrolyte layer forms a gradient distribution from high hydration degree to low hydration degree along the thickness direction. In terms of raw material formulation, silicate cement, as the main cementitious material, provides the ability to generate hydration products such as CSH gel and calcium hydroxide through hydration reaction. The layered structure and nanopores of these hydration products are the physical basis for ion transport.
[0016] Lithium sulfate is selected as the alkali metal salt, and its role is to provide migratable lithium ions for the electrolyte system. After being dissolved in the slurry, lithium sulfate is uniformly dispersed between cement particles. During the hydration process, some lithium ions enter the CSH gel interlayer or are adsorbed on the surface of the hydration products, becoming the ion source for the directional migration of ions under the subsequent electric field drive.
[0017] The layered silicate is made of nano-montmorillonite, which has a natural two-dimensional layered structure with an interlayer spacing of about 1-2 nanometers. After being uniformly dispersed in the slurry, its layers can serve as heterogeneous nucleation sites during the growth of hydration products, guiding the hydration products to grow in the direction of the layers. At the same time, its interlayer can accommodate exchangeable cations, providing additional transport paths and temporary storage sites for lithium ions.
[0018] The raw materials, by weight, are: 100 parts silicate cement, 10-20 parts alkali metal salts, 3-8 parts layered silicates, and 40-45 parts deionized water. A planetary mixer is used for mixing. First, the mixture is stirred at a low speed of 200 rpm for 3 minutes to initially mix the powder and solution. Then, it is stirred at a high speed of 500 rpm for 5 minutes to ensure that all components are evenly dispersed and free of lumps.
[0019] Casting and molding: The mixed slurry is poured into the mold. The inner cavity size of the mold is determined according to the target electrolyte layer size, and the casting thickness is controlled at 3-5 mm. During the casting process, the air bubbles trapped in the slurry are discharged by vibration.
[0020] During the asymmetric curing stage, asymmetric temperature and humidity conditions are applied to the cast green body for curing, causing the cement hydration reaction to proceed at different rates on both sides of the green body, ultimately forming a gradient distribution along the thickness direction from high hydration degree to low hydration degree. The hydration products on the high hydration degree side are dense and structurally complete, with a hydration degree reaching 70%-85%; the low hydration degree side retains a large number of unhydrated cement particles, with a hydration degree of only 30%-45%. After curing, the high hydration degree surface of this cement-based solid electrolyte layer faces the positive electrode in subsequent lamination assembly, while the low hydration degree surface faces the negative electrode.
[0021] Furthermore, the asymmetric temperature and humidity field conditions include: applying differentiated temperature and humidity environments to both sides of the billet, wherein the curing temperature facing the negative electrode side (bottom surface) is controlled at 15-18℃ and the relative humidity is controlled at 60%-70%RH, and the curing temperature facing the positive electrode side (top surface) is controlled at 28-32℃ and the relative humidity is controlled at 90%-95%RH. This condition is achieved using a constant temperature and humidity chamber with zoned temperature and humidity control: a cooling plate and humidity adjustment module are installed at the bottom of the chamber, a heating plate and humidification module are installed at the top, the mold is placed in the middle, the bottom surface is in contact with the low temperature and low humidity zone, and the top surface is exposed to the high temperature and high humidity zone; the curing time lasts for 5-7 days, during which the temperature and humidity parameters on both sides are kept stable; During the curing process, the high temperature and high humidity environment on the top side promotes the full hydration of cement particles and generates a dense CSH gel skeleton; the low temperature and low humidity environment on the bottom side limits the hydration reaction rate, and the cement particles are only partially hydrated on the surface, while the internal unhydrated core remains. Because temperature and humidity transition in a continuous gradient along the thickness of the billet, the degree of hydration also exhibits a continuous gradient distribution from high to low, rather than a distinct stratification.
[0022] S2. The positive electrode, the cement-based solid electrolyte layer, and the negative electrode are stacked in sequence to form a stacked structure. A porous carbon paper layer is provided between the positive electrode and the cement-based solid electrolyte layer as an ion buffer layer. The negative electrode and the cement-based solid electrolyte layer are in direct physical contact. The high hydration degree surface of the cement-based solid electrolyte layer faces the positive electrode and the low hydration degree surface faces the negative electrode. On the positive electrode side, a positive electrode sheet is first prepared or selected. This sheet is made by coating an aluminum foil current collector with a positive electrode active material (such as lithium iron phosphate), a conductive agent, and a binder, and then extending copper terminals. A porous carbon paper layer is then applied to the surface of the positive electrode sheet. This porous carbon paper layer does not participate in the electrochemical reaction; its function is to act as an ion buffer layer, absorbing instantaneous ion concentration fluctuations at the positive electrode / electrolyte interface during subsequent pulse charging, protecting the positive electrode interface from high-concentration shock degradation. Simultaneously, its porous structure provides lateral diffusion paths for lithium ions, promoting uniform ion flux at the interface. The carbon paper layer covers an area consistent with the positive electrode active material region and remains flat and wrinkle-free after placement.
[0023] When placing the electrolyte layer, it is necessary to strictly follow the direction of the gradient hydration degree formed during curing: the high hydration degree surface of the cement-based solid electrolyte layer should face the positive electrode plate side, and the low hydration degree surface should face the negative electrode plate side. The positioning method can be achieved by marking the direction on the mold during curing and retaining the mark after demolding to achieve accurate alignment.
[0024] On the negative electrode side, zinc foil is used as the negative electrode sheet. After the oxide layer is removed by grinding and the surface is cleaned and dried with ethanol, copper terminals are led out. The negative electrode sheet is directly stacked on the low hydration surface of the electrolyte layer without any intermediate layer between them, maintaining direct physical contact so that the unhydrated cement particles in the low hydration surface of the electrolyte layer can fully adhere to the zinc foil surface.
[0025] After the above stacking is completed, aluminum foil is wrapped around the entire stacked structure as an auxiliary current collector and external encapsulation; insulating tape is used to padded the contact points between the aluminum foil and the positive and negative copper terminals to prevent short circuits; the assembled stacked structure is placed in a stainless steel fixture, and an initial clamping pressure of 0.3-0.5MPa is applied by a torque wrench to make each layer physically bonded.
[0026] Furthermore, the setting parameters and working mechanism of the porous carbon paper layer are as follows: The porous carbon paper has a thickness of 50-100μm, a porosity of 60%-80%, a pore size distribution in the micrometer range, and an areal density of 10-30g / m². The selection of this parameter range takes into account both ion buffering capacity and mechanical flexibility: too thick a paper will increase the length of the ion transport path, while too thin a paper will result in insufficient buffering capacity; too high a porosity will reduce mechanical strength, while too low a porosity will result in insufficient ion conduction area. During the pulse charging phase, the intermittent nature of the pulse current causes the ion flux on the positive electrode side to fluctuate periodically. The carbon paper layer acts as an ion buffer, absorbing some lithium ions during the charging pulse and temporarily storing them in its porous structure. During the intermittent period, the ions are slowly released to the electrolyte layer side, thus smoothing the ion concentration gradient at the interface. The high conductivity of the carbon paper layer ensures the effective conduction of electrons from the current collector to the positive electrode active material, while its chemical inertness ensures that it does not participate in electrochemical corrosion in a highly alkaline cement environment.
[0027] S3. Perform an in-situ electrochemical reconstruction and charging procedure on the stacked structure to obtain the reconstructed stacked structure: S301. The stacked structure is charged with a pulsed current. Through the alternating action of the pulsed electric field, alkali metal ions are driven to migrate directionally along the electric field direction inside the cement-based solid electrolyte layer, thereby constructing a directional ion transport channel in situ. S302. Switch to constant voltage charging mode, apply constant voltage and simultaneously increase ambient humidity to the humidity range that triggers secondary hydration reaction, so that the unhydrated cement particles retained in the cement-based solid electrolyte layer generate a hydration product transition layer in situ at the interface between the low hydration surface and the negative electrode sheet. S303. Maintain constant pressure and reduce ambient humidity to dehydrate and densify the hydration product transition layer, thereby obtaining the reconstructed laminated structure; Before the program starts, the completed stacked structure is placed in a controllable humidity test chamber. The initial ambient humidity is set to 60%-70%RH and the temperature is set to 25℃. When the charging program is executed, the stacked structure is in a circuit topology consisting of a DC power supply, a sliding rheostat, an ammeter and a switch connected in series to form the main charging circuit, and a voltmeter connected in parallel across the stacked structure to monitor the voltage in real time. After the switch is closed, the in-situ electrochemical reconstruction charging program is started.
[0028] In the first sub-stage S301, the stacked structure is charged in pulse current mode: the charging power supply is set to output a rectangular wave pulse current with a peak current density of 0.05-0.2mA / cm², a pulse width of 100-150ms, an interval time of 500-800ms, and a total number of pulses of 800-1500. During the entire pulse charging process, the ambient humidity is kept at 60%-70%RH and the temperature is kept at 25℃. As pulse charging proceeds, during the charging pulse, lithium ions are extracted from the positive electrode lithium iron phosphate and enter the cement-based solid electrolyte layer through the porous carbon paper layer. Driven by the electric field, they migrate in a direction perpendicular to the electrolyte layer. During the pulse interval, lithium ions undergo local redistribution under the action of the concentration gradient. However, due to the anisotropic constraint of the montmorillonite two-dimensional plates in the cement-based solid electrolyte layer, the reverse diffusion of lithium ions along the interlayer direction is suppressed, and the concentration bias along the electric field direction is maintained. After hundreds of pulse cycles, lithium ions gradually accumulate in the direction of the electric field to form a stable concentration bias distribution, forming a preferential transport path along the direction perpendicular to the electrolyte layer. In other words, a directional ion transport channel along the direction of the electric field is constructed in situ inside the solidified cement-based solid electrolyte layer.
[0029] In the second sub-stage S302, the charging mode is switched from pulse current to constant voltage mode: a constant voltage of 0.8-1.0V is applied, and the ambient humidity of the test chamber is simultaneously increased from 60%-70%RH to 85%-95%RH for 2-4 hours. Under the synergistic effect of constant pressure and high humidity, water molecules permeate through the nanopores of the cement-based solid electrolyte layer to the interface region on the negative electrode side, and come into contact with the surface of the unhydrated cement particles exposed with low hydration degree. At the same time, the zinc negative electrode undergoes a small amount of electrochemical dissolution under constant pressure of 0.8-1.0V and high alkalinity of the cement matrix, generating Zn²⁺ which enters the alkaline pore solution in the interface region. After the alkaline solution containing Zn²⁺ comes into contact with the unhydrated cement particles, it triggers a secondary hydration reaction to generate zinc-containing CSH gel. This gel grows in situ from the electrolyte layer side to the surface of the zinc negative electrode, gradually filling the mechanical gaps at the interface during the initial stacking assembly, forming a chemically bonded interface transition layer. Under the same voltage and humidity conditions, partial hydroxylation occurs on the surface of lithium iron phosphate on the positive electrode side, while a small amount of unhydrated cement particles on the high hydration side undergo a minor supplementary hydration reaction, forming a moderately fused and stable interface between the positive electrode and the electrolyte layer.
[0030] In the third sub-stage S303, maintain a constant voltage of 0.8-1.0V: reduce the ambient humidity of the test chamber from 85%-95%RH to 40%-50%RH for 1 hour; In the second sub-stage under low humidity, the transition layer of hydration products generated in situ gradually loses water and becomes dense, the zinc-containing CSH gel shrinks in volume and adheres tightly to the zinc anode surface, and the interface structure tends to be stable. The charging current is monitored. When the current drops to less than 10% of the initial current value of the second sub-stage and the current fluctuation is less than 5% and lasts for 30 minutes, the in-situ electrochemical reconstruction charging program is determined to be complete. The switch is then disconnected to end the charging process. The product obtained at this time is the reconstructed stacked structure.
[0031] Furthermore, the pulsed electric field in-situ constructs a directional ion transport channel: the cement hydration product CSH gel has a layered crystal structure with an interlayer spacing of about 1-2 nanometers. The interlayer contains calcium ions and chemically bound water. During the pulse charging phase, lithium ions extracted from the positive electrode migrate directionally along the interlayer of CSH gel under the action of the electric field. Some lithium ions replace the original calcium ion sites in the interlayer to form Li⁺-CSH. Since the radius of Li⁺ is smaller than that of Ca²⁺, the migration barrier of lithium ions in the interlayer is lower, and the ionic conductivity of the area partially replaced by lithium ions is increased. During the pulse intermittent phase, lithium ions undergo reverse diffusion driven by the concentration gradient. However, due to the anisotropic constraint of the montmorillonite layers, the reverse diffusion along the interlayer direction is suppressed, and the concentration gradient along the direction perpendicular to the interlayer direction, i.e., the direction of the electric field, is maintained. After this alternating process is repeated hundreds of times, lithium ions form a stable concentration bias distribution in the direction of the electric field. This is equivalent to building a directional ion transport channel along the direction of the electric field inside the solidified electrolyte. This channel is different from the macroscopic pores formed by physical pore formation. Instead, it is a low-impedance ion transport path formed at the molecular scale through chemical replacement.
[0032] Furthermore, the humidity-electric field synergistic triggering interface in-situ secondary hydration fusion involves unhydrated cement particles retained in the low-hydration surface of the cement-based solid electrolyte layer. These particles, primarily composed of tricalcium silicate and dicalcium silicate, remain dormant under normal temperature and humidity conditions due to insufficient moisture. When a constant voltage of 0.8-1.0V and a high humidity environment of 85%-95%RH are simultaneously applied, the two conditions synergistically trigger the interface reaction. High humidity allows water molecules to penetrate to the negative electrode interface region and come into contact with the exposed unhydrated cement particles at the interface. The constant pressure and highly alkaline environment of the cement matrix cause a small amount of electrochemical dissolution on the zinc negative electrode surface to produce Zn²⁺. The alkaline porous solution containing Zn²⁺ reacts with the unhydrated cement particles to form a zinc-containing CSH gel. This gel grows in situ from the electrolyte layer side to the zinc negative electrode surface and fills the interface gaps. On the positive electrode side, lithium iron phosphate undergoes surface hydroxylation under alkalinity and applied voltage. The unhydrated cement particles on the high hydration side, due to their small content, only undergo a small amount of supplementary hydration reaction, forming a moderately fused and stable interface.
[0033] S4. Perform interface self-healing periodic charge-discharge cycles on the reconstructed stacked structure: After completing N conventional charge-discharge cycles, insert a self-healing cycle. During the self-healing cycle, switch to constant voltage charging mode and simultaneously increase the ambient humidity to the humidity range that triggers the secondary hydration reaction, thereby triggering the supplementary secondary hydration reaction of the unhydrated cement particles to repair the interface microcracks.
[0034] After the Nth cycle of regular charge and discharge is completed, the regular cycle is paused and a self-repair cycle is inserted. The charging mode is switched to constant voltage mode, and a constant voltage of 0.8-1.0V is applied. At the same time, the ambient humidity is increased from 40%-50%RH to 85%-95%RH for 15-30 minutes. This allows water molecules to penetrate through the nanopores of the electrolyte layer to the interface area and come into contact with the unhydrated cement particles exposed at the microcracks caused by the change in electrode volume during the cycle. This triggers a secondary hydration reaction, and the newly generated CSH gel grows in situ at the microcracks and fills the crack space. After the self-repair cycle ends, restore the ambient humidity to 40%-50%RH, maintain constant pressure for 30 minutes to allow the newly formed hydration products to lose water and become dense, and then resume the normal charge and discharge cycle to enter the next round of N cycles. Each subsequent round is performed in this manner.
[0035] Furthermore, the specific process of triggering a secondary hydration reaction during the self-repair cycle is as follows: Under low humidity conditions during normal charge-discharge cycles, the unhydrated cement particles retained in the cement-based solid electrolyte layer are in a dormant state due to insufficient moisture and will not spontaneously undergo hydration reactions. When the self-healing cycle is initiated and the ambient humidity is increased to 85%-95%RH, water molecules penetrate into the interface region through the nanopores of CSH gel in the electrolyte layer and the microcrack channels generated during the cycle, and come into contact with the surface of unhydrated cement particles exposed on both sides of the microcracks. The main mineral components of unhydrated cement particles are tricalcium silicate and dicalcium silicate. When they come into contact with water, they undergo a hydration reaction to generate CSH gel and calcium hydroxide. The newly generated CSH gel gradually grows from both sides to the middle in the narrow space of the microcrack and overlaps with each other, eventually filling the entire crack space. Since the chemical composition of the newly formed hydration products is consistent with the original hydration product matrix of the electrolyte layer, the two form a continuous inorganic bond at the interface. The repaired area is basically the same as the uncracked area in terms of ion conduction performance and mechanical strength. After the self-repair cycle ends, the humidity is restored to a low-humidity state, the newly formed hydration products lose water and become dense, and the microcracks are permanently filled.
[0036] Furthermore, the range of N values from 15 to 30 is based on the following considerations: During normal charge-discharge cycles, the positive electrode lithium iron phosphate undergoes volume changes due to the insertion and extraction of lithium ions, and the negative electrode zinc foil undergoes dissolution and deposition during charge-discharge. These two effects generate cyclic stress at the interface between the electrode and the electrolyte layer. As the number of cycles increases, the interface stress gradually accumulates. When the accumulated stress exceeds the tensile strength of the hydration product gel, microcracks begin to appear at the interface. When N=15-30 times, the width of the microcrack is usually in the range of hundreds of nanometers to several micrometers, which is within the scale range that hydration products can fill and repair. At this time, initiating the self-healing cycle can effectively fill the crack and restore the continuity of the interface. If the N value is too small, the self-repair process will be triggered frequently before the microcracks have fully formed. The repeated alternation of high humidity and low humidity will cause the water content of the electrolyte layer to fluctuate frequently, affecting the stability of ion transport. If the N value is too large, the microcracks will gradually expand into through-cracks under the continuous action of cyclic stress. The crack width will exceed the range that the hydration products can fill in a single growth, and the self-healing effect will be reduced.
[0037] Based on the above method, this application also discloses a cement-based solid electrolyte multilayer structure energy storage system, with reference to... Figure 5 The cement-based solid electrolyte stacked energy storage system shown includes: The gradient hydration degree electrolyte layer preparation module is used to mix silicate cement, alkali metal salt, layered silicate and water to obtain slurry, and after casting and molding, it is cured under asymmetric temperature and humidity field conditions so that the obtained cement-based solid electrolyte layer forms a gradient distribution from high hydration degree to low hydration degree along the thickness direction. An asymmetric stacked structure assembly module is used to stack a positive electrode, a cement-based solid electrolyte layer, and a negative electrode in sequence to form a stacked structure. A porous carbon paper layer is set between the positive electrode and the cement-based solid electrolyte layer as an ion buffer layer. The negative electrode and the cement-based solid electrolyte layer are in direct physical contact, and the high hydration degree surface of the cement-based solid electrolyte layer faces the positive electrode and the low hydration degree surface faces the negative electrode. An in-situ electrochemical reconstruction charging control module is used to execute an in-situ electrochemical reconstruction charging program on the stacked structure. The in-situ electrochemical reconstruction charging control module is configured to: firstly charge the stacked structure with a pulsed current, and through the alternating action of the pulsed electric field, drive alkali metal ions to migrate directionally along the electric field direction inside the cement-based solid electrolyte layer, and construct directional ion transport channels in situ; then switch to a constant voltage charging mode, apply a constant voltage and simultaneously increase the ambient humidity to the humidity range that triggers the secondary hydration reaction, so that the unhydrated cement particles retained in the cement-based solid electrolyte layer generate a hydration product transition layer in situ at the interface between the low hydration degree surface and the negative electrode sheet; then maintain the constant voltage and reduce the ambient humidity, so that the hydration product transition layer loses water and becomes dense, thus obtaining the reconstructed stacked structure; The self-healing cycle control module is used to perform interface self-healing periodic charge-discharge cycles on the reconstructed stacked structure. The self-healing cycle control module is configured to insert a self-healing cycle after completing N regular charge-discharge cycles. During the self-healing cycle, it switches to constant voltage charging mode and simultaneously increases the ambient humidity to the humidity range that triggers the secondary hydration reaction, thereby triggering the supplementary secondary hydration reaction of the unhydrated cement particles to repair the interface microcracks.
[0038] See Figure 6 This is a schematic diagram of the structure of an electronic device provided in an embodiment of this application. Figure 6 As shown, the electronic device 1000 may include: at least one processor 1001, at least one communication bus 1002, a temperature and humidity sensor interface 1003, a voltage and current detection interface 1004, a programmable power drive interface 1005, and a memory 1006.
[0039] The temperature and humidity sensor interface 1003 is used to connect a temperature and humidity sensor to collect real-time temperature and relative humidity data of the environment in which the stacked structure is located, and transmit the collected data to the processor 1001. The voltage and current detection interface 1004 is used to connect a voltmeter and an ammeter to monitor the voltage across the stacked structure and the current in the charging circuit in real-time, and transmit the monitoring data to the processor 1001. The programmable power supply drive interface 1005 is used to connect a programmable DC power supply, receive control commands from the processor 1001, and output a pulse current with a specified waveform, peak current density, pulse width, and interval time, or output a constant voltage with a specified voltage value to the stacked structure.
[0040] The memory 1006 stores a computer program that can run on the processor 1001. When the processor 1001 executes the computer program, it implements the complete process of S1 to S4 in the above method embodiment. Specifically, it includes: controlling the programmable power supply to output pulse current to perform pulse charging in stage S301; controlling the programmable power supply to switch to constant voltage output and simultaneously increasing the ambient humidity through the humidity adjustment device to perform stage S302; controlling the humidity adjustment device to decrease the ambient humidity to perform stage S303; and in stage S4, periodically switching between the normal charge-discharge cycle and the self-repair cycle according to a preset N value, and completing the interface self-repairing periodic charge-discharge cycle through the coordinated control of the programmable power supply and the humidity adjustment device.
[0041] The processor 1001 is connected to the temperature and humidity sensor interface 1003, the voltage and current detection interface 1004, the programmable power supply drive interface 1005, and the memory 1006 via the communication bus 1002. It is responsible for coordinating the work of each module, receiving sensor data, running computer programs, and sending control commands to the programmable power supply and humidity control device according to the program logic. Through the cooperation of the aforementioned hardware interfaces and computer programs, this electronic device achieves automated control of the energy storage process in the cement-based solid electrolyte stacked structure, enabling the in-situ electrochemical reconstruction charging program and self-repair cycle to be executed precisely according to preset parameters.
[0042] This invention also provides a computer-readable storage medium storing a computer program, which, when executed by a processor, implements the steps of the cement-based solid electrolyte stacked structure energy storage method described in any of the above method embodiments.
[0043] The computer-readable storage medium includes, but is not limited to, various media capable of storing program code, such as USB flash drives, portable hard drives, read-only memory (ROM), random access memory (RAM), magnetic disks, or optical disks. The computer program includes program instructions that, when executed by the processor, control the programmable power supply connected to the processor to output pulsed current or constant voltage, control the humidity control device to adjust ambient humidity, and periodically switch between regular charge-discharge cycles and self-repair cycles. This completes the automated execution of the in-situ electrochemical reconstruction charging procedure (S3) and the interface self-repairing periodic charge-discharge cycle (S4) in the cement-based solid electrolyte stacked structure energy storage method.
[0044] Secondly: The accompanying drawings of the embodiments disclosed in this invention only involve the structures involved in the embodiments disclosed in this invention. Other structures can refer to the general design. In the absence of conflict, the same embodiment and different embodiments of this invention can be combined with each other. In conclusion, the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for storing electricity using a cement-based solid electrolyte multilayer structure, characterized in that, include: S1. Silicate cement, alkali metal salt, layered silicate and water are mixed and stirred to obtain a slurry. After being cast into shape, it is cured under asymmetric temperature and humidity field conditions so that the resulting cement-based solid electrolyte layer forms a gradient distribution from high hydration degree to low hydration degree along the thickness direction. S2. The positive electrode, the cement-based solid electrolyte layer, and the negative electrode are stacked in sequence to form a stacked structure. A porous carbon paper layer is provided between the positive electrode and the cement-based solid electrolyte layer as an ion buffer layer. The negative electrode and the cement-based solid electrolyte layer are in direct physical contact. The high hydration degree surface of the cement-based solid electrolyte layer faces the positive electrode and the low hydration degree surface faces the negative electrode. S3. Perform an in-situ electrochemical reconstruction and charging procedure on the stacked structure to obtain the reconstructed stacked structure: S301. The stacked structure is charged with a pulsed current. Through the alternating action of the pulsed electric field, alkali metal ions are driven to migrate directionally along the electric field direction inside the cement-based solid electrolyte layer, thereby constructing a directional ion transport channel in situ. S302. Switch to constant voltage charging mode, apply constant voltage and simultaneously increase ambient humidity to the humidity range that triggers secondary hydration reaction, so that the unhydrated cement particles retained in the cement-based solid electrolyte layer generate a hydration product transition layer in situ at the interface between the low hydration surface and the negative electrode sheet. S303. Maintain constant pressure and reduce ambient humidity to dehydrate and densify the hydration product transition layer, thereby obtaining the reconstructed laminated structure; S4. Perform interface self-healing periodic charge-discharge cycles on the reconstructed stacked structure: After completing N conventional charge-discharge cycles, insert a self-healing cycle. During the self-healing cycle, switch to constant voltage charging mode and simultaneously increase the ambient humidity to the humidity range that triggers the secondary hydration reaction, thereby triggering the supplementary secondary hydration reaction of the unhydrated cement particles to repair the interface microcracks.
2. The method for storing electricity using a cement-based solid electrolyte multilayer structure according to claim 1, characterized in that, The asymmetric temperature and humidity field conditions include: Set the bottom surface of the casting mold to face the negative electrode side and place it in a low-temperature, low-humidity environment. Control the curing temperature at 15-18℃ and the relative humidity at 60%-70%RH. Set the top surface of the casting mold to face the positive electrode side and place it in a high-temperature, high-humidity environment. Control the curing temperature at 28-32℃ and the relative humidity at 90%-95%RH. The curing time should last for 5-7 days, during which time the temperature and humidity parameters on both sides should be kept stable. During the curing process, the high temperature and high humidity environment on the top side promotes the full hydration of cement particles. The hydration product CSH gel develops densely and overlaps to form a continuous skeleton, resulting in a hydration degree of 70%-85% on this side. On the bottom side, the low temperature and low humidity environment limits the hydration reaction rate and water supply. Only the surface of the cement particles undergoes partial hydration, while a large number of unhydrated nuclei remain inside, resulting in a hydration degree of only 30%-45% on this side. As the temperature and humidity transition continuously along the thickness of the electrolyte layer, the hydration degree also changes continuously from the high hydration degree side to the low hydration degree side, forming a gradient hydration degree distribution along the thickness direction. The asymmetric temperature and humidity field conditions are achieved by a constant temperature and humidity chamber with zoned temperature and humidity control functions. The bottom of the constant temperature and humidity chamber is equipped with a cooling plate and a humidity adjustment module to provide a low temperature and low humidity environment, and the top is equipped with a heating plate and a humidification module to provide a high temperature and high humidity environment. The casting mold is placed in the middle of the chamber, with the bottom surface in contact with the low temperature and low humidity zone and the top surface exposed to the high temperature and high humidity zone.
3. The method for storing electricity using a cement-based solid electrolyte multilayer structure according to claim 1, characterized in that, The porous carbon paper layer includes: The porous carbon paper layer is placed between the positive electrode sheet and the cement-based solid electrolyte layer. The porous carbon paper layer has a thickness of 50-100 μm, a porosity of 60%-80%, a surface density of 10-30 g / m², and a pore size distribution in the micrometer range. The porous carbon paper layer completely covers the active material area of the positive electrode sheet, and remains flat and wrinkle-free after placement. One side of the paper is attached to the surface of the active material of the positive electrode sheet, and the other side is attached to the high hydration surface of the cement-based solid electrolyte layer. The porous carbon paper layer acts as an ion buffer during the pulsed current charging phase. During the charging pulse, it absorbs and temporarily stores some of the alkali metal ions released from the positive electrode side. During the pulse interval, it slowly releases these ions to the cement-based solid electrolyte layer side to smooth the ion concentration gradient at the positive electrode / electrolyte interface, buffer the instantaneous ion concentration fluctuations caused by pulsed charging, and avoid interfacial overpotential and side reactions caused by local concentration polarization. At the same time, its porous structure provides a path for alkali metal ions to diffuse laterally along the interface, promoting a uniform distribution of ion flux at the interface.
4. The method for storing electricity using a cement-based solid electrolyte multilayer structure according to claim 1, characterized in that, The charging of the stacked structure includes: The pulse waveform adopts a rectangular wave, the peak current density is controlled at 0.05-0.2mA / cm², the pulse width is 100-150ms, the interval time is 500-800ms, and the total number of pulses is 800-1500. During the charging pulse, alkali metal ions are extracted from the positive electrode and injected into the cement-based solid electrolyte layer through the porous carbon paper layer. Driven by the electric field, they migrate directionally in a direction perpendicular to the electrolyte layer. During the pulse interval, alkali metal ions undergo local relaxation and redistribution under the anisotropic constraints of the concentration gradient and the layered silicates in the cement-based solid electrolyte layer. This causes the concentration bias of alkali metal ions to gradually accumulate along the electric field direction. After hundreds of pulse cycles, a directional ion transport channel along the electric field direction is constructed in situ inside the solidified cement-based solid electrolyte layer.
5. The method for storing electricity using a cement-based solid electrolyte multilayer structure according to claim 1, characterized in that, The switching of the constant voltage charging mode and the increase in ambient humidity include: After the pulse current charging phase ends, switch the charging mode to constant voltage mode, apply a constant voltage of 0.8-1.0V, and simultaneously increase the ambient humidity from 60%-70%RH to 85%-95%RH for 2-4 hours. In this stage, the humidity enhancement must be performed after the S301 directional ion transport channel is established to avoid uncontrollable full hydration leading to channel blockage when the ion channel is not directional. The enhanced high humidity environment allows water molecules to penetrate through the nanopores of the cement-based solid electrolyte layer to the negative electrode interface region and contact the surface of the unhydrated cement particles exposed with low hydration degree. At the same time, under the combined action of constant voltage of 0.8-1.0V and the highly alkaline environment of the cement matrix, a small amount of electrochemical dissolution occurs on the zinc negative electrode surface to generate Zn²⁺. The alkaline pore solution containing Zn²⁺ triggers a secondary hydration reaction after contacting the unhydrated cement particles, generating a zinc-containing CSH gel. This gel grows in situ from one side of the electrolyte layer towards the zinc negative electrode surface, filling the mechanical gaps at the interface during the initial stacking assembly and forming a chemically bonded interface with ion conduction and mechanical interlocking. Under alkaline conditions and applied voltage, partial hydroxylation occurs on the surface of lithium iron phosphate on the positive electrode side, while a small amount of unhydrated cement particles on the high hydration side undergo a minor supplementary hydration reaction, forming a moderately fused and stable interface.
6. The method for storing electricity using a cement-based solid electrolyte multilayer structure according to claim 1, characterized in that, Maintaining constant pressure and reducing ambient humidity includes: After the constant pressure-high humidity stage is completed, maintain a constant pressure of 0.8-1.0V and reduce the ambient humidity from 85%-95%RH to 40%-50%RH for 1 hour. In a low-humidity environment, the transition layer of hydration products generated in situ during the S302 stage gradually loses water and becomes dense, and the zinc-containing CSH gel shrinks and adheres tightly to the negative electrode surface, making the interface structure tend to be stable. When the charging current drops to less than 10% of the initial value and the fluctuation range is less than 5% for 30 minutes, the in-situ electrochemical reconstruction charging process is considered complete, and the reconstructed stacked structure is obtained.
7. The method for storing electricity using a cement-based solid electrolyte multilayer structure according to claim 1, characterized in that, The interface self-healing periodic charge-discharge cycle includes: The conventional charge-discharge cycle adopts constant current-constant voltage charging and constant current discharging modes. During charging, it is charged at a constant current of 0.2C to 1.5V, and then switched to constant voltage charging until the current drops below 0.01C to cut off. During discharging, it is discharged at a constant current of 0.2C to 0.5V to cut off. During the charging and discharging process, the ambient temperature is maintained at 25℃ and the relative humidity is 40%-50%RH. The value of N ranges from 15 to 30 times. After the Nth cycle of the normal charge-discharge cycle is completed, the self-repair cycle is inserted. The self-repair cycle is executed as follows: stop the normal charge-discharge operation, switch to constant voltage charging mode, apply a constant voltage of 0.8-1.0V, and simultaneously increase the ambient humidity from 40%-50%RH to 85%-95%RH for 15-30 minutes. Then, restore the ambient humidity to 40%-50%RH and maintain constant voltage for 30 minutes to allow the newly formed hydration products to lose water and become dense. Then, resume the normal charge-discharge cycle and enter the next round of N cycles. During the self-healing cycle, the increased humidity allows water molecules to penetrate into the interface region and come into contact with the unhydrated cement particles exposed at the interface microcracks caused by electrode volume changes and cyclic stress during the charge-discharge cycle. This triggers a secondary hydration reaction, and the newly generated CSH gel grows in situ at the microcracks and fills the crack space.
8. A cement-based solid electrolyte multilayer energy storage system, characterized in that, include: The gradient hydration degree electrolyte layer preparation module is used to mix silicate cement, alkali metal salt, layered silicate and water to obtain slurry, and after casting and molding, it is cured under asymmetric temperature and humidity field conditions so that the obtained cement-based solid electrolyte layer forms a gradient distribution from high hydration degree to low hydration degree along the thickness direction. An asymmetric stacked structure assembly module is used to stack a positive electrode, a cement-based solid electrolyte layer, and a negative electrode in sequence to form a stacked structure. A porous carbon paper layer is set between the positive electrode and the cement-based solid electrolyte layer as an ion buffer layer. The negative electrode and the cement-based solid electrolyte layer are in direct physical contact, and the high hydration degree surface of the cement-based solid electrolyte layer faces the positive electrode and the low hydration degree surface faces the negative electrode. An in-situ electrochemical reconstruction charging control module is used to execute an in-situ electrochemical reconstruction charging program on the stacked structure. The in-situ electrochemical reconstruction charging control module is configured to: firstly charge the stacked structure with a pulsed current, and through the alternating action of the pulsed electric field, drive alkali metal ions to migrate directionally along the electric field direction inside the cement-based solid electrolyte layer, and construct directional ion transport channels in situ; then switch to a constant voltage charging mode, apply a constant voltage and simultaneously increase the ambient humidity to the humidity range that triggers the secondary hydration reaction, so that the unhydrated cement particles retained in the cement-based solid electrolyte layer generate a hydration product transition layer in situ at the interface between the low hydration degree surface and the negative electrode sheet; then maintain the constant voltage and reduce the ambient humidity, so that the hydration product transition layer loses water and becomes dense, thus obtaining the reconstructed stacked structure; The self-healing cycle control module is used to perform interface self-healing periodic charge-discharge cycles on the reconstructed stacked structure. The self-healing cycle control module is configured to insert a self-healing cycle after completing N regular charge-discharge cycles. During the self-healing cycle, it switches to constant voltage charging mode and simultaneously increases the ambient humidity to the humidity range that triggers the secondary hydration reaction, thereby triggering the supplementary secondary hydration reaction of the unhydrated cement particles to repair the interface microcracks.
9. An electronic device, characterized in that, include: At least one processor, at least one communication bus, a temperature and humidity sensor interface, a voltage and current detection interface, a programmable power drive interface, and a memory; And a computer program stored in the memory and executable on the processor, wherein the computer program, when executed by the processor, implements the cement-based solid electrolyte stacked structure energy storage method according to any one of claims 1 to 7.
10. A computer-readable storage medium, characterized in that, The computer-readable storage medium stores a computer program that, when executed by a processor, implements the cement-based solid electrolyte stacked structure energy storage method according to any one of claims 1 to 7.